Creating nanoporosity in silver nanocolumns by direct exposure to radio-frequency air plasma. Issue 1 (27th November 2015) - El Mel, Abdel-Aziz; Stephant, Nicolas; Hamon, Jonathan; Thiry, Damien; Chauvin, Adrien; Chettab, Meriem; Gautron, Eric; Konstantinidis, Stephanos; Granier, Agnès; Tessier, Pierre-Yves
Abstract : In this communication we report for the first time on the possibility of generating nanoporosity in silver nanocolumns using a dry approach based on the oxidation of silver by direct exposure to a commercially available radio-frequency air plasma. Abstract : Nanoporous materials are of great importance for a broad range of applications including catalysis, optical sensors and water filtration. Although several approaches already exist for the creation of nanoporous materials, the race for the development of versatile methods, more suitable for the nanoelectronics industry, is still ongoing. In this communication we report for the first time on the possibility of generating nanoporosity in silver nanocolumns using a dry approach based on the oxidation of silver by direct exposure to a commercially available radio-frequency air plasma. The silver nanocolumns are created by glancing angle deposition using magnetron sputtering of a silver target in pure argon plasma. We show that upon exposure to the rf air plasma, the nanocolumns transform from solid silver into nanoporous silver oxide. We further show that by tuning the plasma pressure and the exposure duration, the oxidation process can be finely adjusted allowing for precisely controlling the morphology and the nanoporosity of the silver oxide nanocolumns. The generation of porosity within the silver nanocolumns is explained according to a cracking-induced oxidation mechanism based on two repeated events occurring alternately during the oxidation process: (i) oxidation of silver upon exposure to the air plasma and (ii) generation of nanocracks and blisters within the oxide layer due to the high internal stress generated within the material during oxidation.